Floods areas in the paulista region of river basin Paraiba do sul and headwaters of Rural Environmental Register - Coutinho, Marcos Pellegrini; Gonçalves, Demerval Aparecido; De Oliveira Caram, Rochane; Soares, Paulo Valladares [UNESP] (FapUNIFESP (SciELO), 2018)
The knowledge of urban flood risk areas associated with the rural environmental register database allows to identify where small rivers begins. This article combines and assesses the risk prone areas with headwaters and proposes actions. The goal of this work was to evaluate the relationships between flood risk and the environmental conditions of headwaters (both in preserved, consolidated areas and to be reforested) of 10 municipalities in the Paraiba Valley, previously mapped by the Institute of Technological Research (IPT). The results showed that, for the municipalities evaluated, 10,324 headwaters were registered and, for all municipalities the quantity of preserved areas is higher in comparison with the consolidated areas. Furthermore, there is a lack of vegetation restoration project in rivers that causes flooding in the studied municipalities, even after changes in the Brazilian Forest Code. These results provide valuable information to the local institutions that conduct actions for the restoration of deforested areas and several other initiatives that aim to mitigate flood risk in the areas assessed in this study.
Áreas de inundação no trecho paulista da bacia do Rio Paraíba do Sul e nascentes do Cadastro Ambiental Rural
Keywords: Floods; Headwaters; Hydrographic basin river; Paraíba do Sul; Rural Environmental Register